Hyperuricemia Is an Independent Risk Factor for Erectile Dysfunction. Issue 7 (1st July 2016) - Long, Hao; Jiang, Jun; Xia, Jiyi; Jiang, Rui; He, Yanzheng; Lin, Haocheng; Fan, Zhongcai; Zeng, Tiebing
ABSTRACT: Introduction: Hyperuricemia may be related to the development of endothelial dysfunction and cardiovascular diseases. However, the association between hyperuricemia and erectile dysfunction (ED) is not currently clear. Aim: The goal of this study is to investigate the effect of hyperuricemia on erectile function and possible mechanisms. Methods: Twenty-four 8-week-old male SD rats were randomly divided into 4 groups. Group A (control): Rats received normal saline and served as controls. Group B (hyperuricemia): rats were given oxonic acid 250 mg/kg bw/day through gastric gavage for 4 weeks. Group C (febuxostat): normal rats were treated with 5 mg/kg febuxostat through gastric gavage for 4 weeks. Group D (hyperuricemia + Febuxostat): normal rats were treated with 250 mg/kg bw/day oxonic acid and 5 mg/kg bw/day febuxostat with 1 hour interval for 4 weeks. Measurements: The level of serum uric acid, the maximum intracavernosal pressure (ICPmax), mean arterial pressure (MAP), and the expression of endothelial nitric oxide synthase (eNOS), phospho-eNOS, neuronal NOS, Rho-associated protein kinaise (ROCK)1 and ROCK2 and the level of nitric oxide (NO) and reactive oxygen species (ROS) in cavernous tissue were determined. Results: The level of serum uric acid and ROS in hyperuricemic rats was significantly higher than that in the other 3 groups ( P < .05). After electrostimulation with 3 and 5 voltage, the ratio of ICPmax/MAP in hyperuricemic rats was significantly less than that in other 3 groups ( P < .05), respectively. eNOS, p-eNOS, and nNOS expression in hyperuricemic rats were significantly decreased compared to the other 3 groups ( P < .05), respectively. Conclusion: Erectile function is impaired by hyperuricemia. The decrease of eNOS, p-eNOS, and nNOS protein expression and increase of ROS in cavernous tissue may be one of the key mechanisms of ED caused by hyperuricemia.